Mapping region in early American writing - Watts, Edward, 1964-; Holt, Keri; Funchion, John; ebrary, Inc. (Athens : University of Georgia Press, 2015)
"The essays collected in Mapping Region in Early American Writing study how American writers thought about the spaces around them. The contributors reconsider the various roles regions--imagined politically, economically, racially, and figuratively--played in the formation of American communities, both real and imagined. The texts they study--some canonical, others archival, some literary, others scientific, polemical, or documentary--create and reveal important mental mappings and cartographies that reveal how a diversity of populations imagined themselves, their communities, and their nation as occupying various places in the American landscape"--Provided by publisher.
Introduction: Bordering establishments: mapping and charting region before 1860 / Edward Watts and Keri Holt -- Section 1. Chartings : colonies and countries -- "To plant himself in with soveranity" : Welsh Indians and the early West, 1576-1812 / Edward Watts -- Reading the routes : early American nature writing and critical regionalism before the "postfrontier" / William V. Lombardi -- The "humor of the Old Southwest" and national regionality / Robert Gunn -- West Indian emancipation and the time of regionalism in the hemispheric 1850s / Martha Schoolman -- Section 2. Mappings : creating places -- The labor of regions : a comparative analysis of the economic and literary production of three southern regions in the eighteenth-century Atlantic world / Steven W. Thomas -- Captive in Mexico : Zebulon Pike and the new American regionalism / Andy Doolen -- On the Hudson River line : postrevolutionary regionalism, neo-Tory sympathy, and "A lady of the State of New York" / Duncan Faherty -- "I was now living in a new world" : Frederick Douglass, Herman Melville, and New Bedford's cosmopolitan locality / Jennifer Schell -- Section 3. Countermappings : new spaces in old places -- Tribal Christianity : the second Great Awakening and William Apess's backwoods Methodism / Harry Brown -- "We, too, the people" : rewriting resistance in the Cherokee Nation / Keri Holt -- African American literature of the Gold Rush / Janet Neary and Hollis Robbins -- Postscript: Creole adjudication : governing New Orleans and regional provisionality in the long nineteenth century / John Funchion.
Includes bibliographical references (pages 269-293) and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: American literature -- Colonial period, ca. 1600-1775 -- History and criticism; American literature -- Revolutionary period, 1775-1783 -- History and criticism; American literature -- 1783-1850 -- History and criticism; Regionalism in literature; Space perception in literature; Landscapes in literature; Geographical perception in literature; Community life in literature; Electronic books